Effect of spherical Au nanoparticles on nanofriction and wear reduction in dry and liquid environments - Maharaj, Dave; Bhushan, Bharat (Beilstein Journal of Nanotechnology, 2012)
Nano-object additives are used in tribological applications as well as in various applications in liquids requiring controlled manipulation and targeting. On the macroscale, nanoparticles in solids and liquids have been shown to reduce friction and wear. On the nanoscale, atomic force microscopy (AFM) studies have been performed in single- and multiple-nanoparticle contact, in dry environments, to characterize friction forces and wear. However, limited studies in submerged liquid environments have been performed and further studies are needed. In this paper, spherical Au nanoparticles were studied for their effect on friction and wear under dry conditions and submerged in water. In single-nanoparticle contact, individual nanoparticles, deposited on silicon, were manipulated with a sharp tip and the friction force was determined. Multiple-nanoparticle contact sliding experiments were performed on nanoparticle-coated silicon with a glass sphere. Wear tests were performed on the nanoscale with AFM as well as on the macroscale by using a ball-on-flat tribometer to relate friction and wear reduction on the nanoscale and macroscale. Results indicate that the addition of Au nanoparticles reduces friction and wear.
Keywords: AFM; drug delivery; friction; gold nanoparticles; MEMS/NEMS; nanomanipulation